Asuhan Keperawatan Jiwa pada Pasien dengan Resiko Perilaku Kekerasan di Wisma Cendrawasih RSJ Prof. Dr. HB. Sa’anin Padang - Windy Suryaningsih Amazihono; Dwi Happy Anggia Sari; Vivi Yuderna; Ramaita . (CV. ITTC INDONESIA, 2026)
The risk of violent behavior is one of the common nursing problems found in patients with mental disorders and has the potential to harm themselves, others, and the environment. This study aims to describe psychiatric nursing care for patients at risk of violent behavior. The method used is a case study of patients, who was treated at Prof. Dr. HB Saanin Mental Hospital in Padang for 5 days, from February 2 to February 7, 2026. The assessment results showed three nursing diagnoses: risk of violent behavior, hallucinations, and self-care deficit. Nursing interventions were carried out using implementation strategies (SP) 1 to 4, which included physical exercises, medication adherence, verbal approaches, and spiritual approaches. The evaluation results indicated a decrease in the signs and symptoms of violent behavior risk; the patient became calmer, was able to control emotions, and showed improved ability to perform self-care independently. It can be concluded that the implementation strategies are effective in helping patients control violent behavior and improve their independence. Additionally, family and environmental support play an important role in maintaining the outcomes achieved by the patient.